FACTORS IN DETERIORATING INVENTORY MODELS :A LITERATURE REVIEW ANALYSIS - Dr. Vandana Kumari (Innovative Research Thoughts, 2022)
No business association can keep running without Inventory. Harris (1993) presented the existing style monetary request quantity (EOQ) design wherein request is constant. After the job of his numerous explores took a go at this region and have created distinctive inventory design to catch numerous engaging as well as authentic circumstances. Likewise, during typical capacity period, the presentation of certain things decayed after some time. Keywords: Inventory, numerous, capacity, review, models